IMPROVING DIGITAL MARKETING FOR MICRO ENTERPRISES IN SEGORO TAMBAK VILLAGE: A COMMUNITY ENGAGEMENT - Gilbert, Warren; Suyanto, Suyanto (LP2M Universitas Ibrahimy, 2025)
Digital marketing is an essential strategy for microenterprises to expand market share and increase sales. To support micro enterprises in Segoro Tambak Village, Sedati Subdistrict, Sidoarjo Regency, a community engagement program was implemented through the national grant. The program involved preliminary observations, digital marketing workshops, interviews, hands-on training, mentoring, and follow-up activities. As part of the intervention, Instagram and TikTok accounts were created for 20 micro enterprises, enabling them to showcase their products and reach broader audiences. Pre- and post-program assessments indicated significant improvements: over 73% of participants reported increased confidence in using social media, while 75% successfully uploaded promotional content independently after mentoring. Two key outcomes emerged from the engagement: (1) the establishment of social media accounts for both the village group and individual micro firms, and (2) enhanced knowledge and digital literacy among participants, particularly those previously unfamiliar with smartphone-based marketing. These results demonstrate how structured community-based interventions can effectively bridge the digital divide, empower local entrepreneurs, and increase product visibility and sales. Beyond immediate benefits, this initiative contributes to the long-term sustainability and competitiveness of micro enterprises in adapting to the rapidly evolving digital economy.